The suffering of chronic pain patients on a wait list: Are they amenable to narrative therapy?. Issue 1 (1st January 2017) - Carr, Eloise C. J.; McCaffrey, Graham; Ortiz, Mia Maris
ABSTRACT: Background : Chronic pain affects one in five Canadians. People with chronic pain frequently experience loss in their lives related to work, relationships, and their independence. They may be referred to a chronic pain program, which aims to strengthen coping through medical intervention and self-management skills. Data suggest that, even when individuals begin their pain program, many feel overwhelmed and do not continue. Aims : The aim of this study was to conduct a needs assessment to explore the acceptability and feasibility of developing a psychosocial intervention, narrative therapy (NT), to address loss for chronic pain patients on the wait list of a chronic pain program. Methods : Two focus groups were conducted with ten patients who had experienced being on a wait list for a provincial chronic pain management program (CPMP). Transcribed interviews were subjected to thematic and interpretive analysis. Results : Two major themes emerged from the analysis: loss of identity and sharing a story of chronic pain. All patients were enthusiastic toward an NT intervention, although individual preferences differed regarding mode of delivery. Conclusions : Loss is a significant part of the chronic pain experience. NT seems to be an acceptable intervention to address loss for patients on the wait list for a chronic pain program.